The Relationship Between Personality Traits, Flow-Experience, and Different Aspects of Practice Behavior of Amateur Vocal Students - Heller, Katharina; Bullerjahn, Claudia; von Georgi, Richard (Frontiers in Psychology, 2015)
Most of the existing studies on musical practice are concerned with instrumentalists only. Since singers are seldom considered in research, the present study is based on an online-sample of amateur vocal students (N = 120; 92 female, 28 male). The study investigated the correlations between personality traits, flow-experience and several aspects of practice characteristics. Personality was represented by the three personality dimensions extraversion, neuroticism and psychoticism, assessed by Eysenck’s Personality Profiler as well as the trait form of the Positive and Negative Affect Schedule. ‘Flow-experience’, ‘self-congruence’ and ‘fear of losing control over concentration’, assessed by the Practice Flow Inventory, served as variables for flow-experience. The practice motivation was measured by the Practice Motivation Questionnaire in four categories (‘self’, ‘group’, ‘audience’, ‘teacher’). In addition, the Practice Behavior Questionnaire was used to provide an insight into the practice situation and behavior of singing students. The results show significant correlations: Participants with high extraversion-scores experience significantly more flow than less extraverted persons, whereas lesser flow-experience seems to be related to high neuroticism-scores. Nevertheless, there is no influence in flow-experience concerning singing style (‘classical’ or ‘popular’). The longer the practicing time, the more likely students are to achieve flow-experience. However, older singers tend to have less flow-experience. Consequently, singers seem to differ in their personality and practice behavior compared to other musicians. Most of the findings show that having control over one’s instrument is decisive for achieving a performance of high quality, especially for singers. On the other hand, certainty in handling an instrument is essential to arouse a flow-feeling. However, flow-experience seems to be common mainly with amateur singers. In conclusion, this offers a starting point for new research on the psychology of vocalists in greater depth.